2006
DOI: 10.1111/j.1468-3156.2005.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of engagement and barriers to physical activity in a population of adults with learning disabilities

Abstract: This study examined levels of, and barriers to, physical activity in a population of 19 adults with learning disabilities living in community supported accommodation, using diary records and semi-structured interviews with staff. The levels of physical activity were higher in the sample population than previous figures for adults with learning disabilities, but lower than figures for the general population. The five main barriers to physical activity identified by staff were: clients' lack of understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 16 publications
4
47
0
Order By: Relevance
“…This is consistent with the available evidence in that adults with intellectual disabilities engage in low levels of physical activity . The barriers reported for participation in physical activity for individuals with intellectual disabilities include a lack of understanding of the benefits or regular physical activity, a lack of awareness of available physical activity options, financial limitations and limited transport and staffing . It is important that future studies are developed that take into consideration these barriers and aim to overcome the difficulties for adults with intellectual disabilities in participating in regular physical activity.…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with the available evidence in that adults with intellectual disabilities engage in low levels of physical activity . The barriers reported for participation in physical activity for individuals with intellectual disabilities include a lack of understanding of the benefits or regular physical activity, a lack of awareness of available physical activity options, financial limitations and limited transport and staffing . It is important that future studies are developed that take into consideration these barriers and aim to overcome the difficulties for adults with intellectual disabilities in participating in regular physical activity.…”
Section: Discussionsupporting
confidence: 81%
“…These results regarding physical fitness do not confirm the developmental skilllearning hypothesis, which states that the developmental skill-learning gap widens for children with less physical skill as their age-group peers, on average, gain expertise and start to participate in more demanding physical activities (Wall 2004). In addition, several studies have shown that individuals with ID experience barriers for physical activity, such as lack of motivation to participate (Temple & Walkley 2007), immobility and illness (Finlayson et al 2009), inadequate support and opportunities, problems with transport (Caton et al 2012) or financial constraints (Hawkins & Look 2006). The low performance on motor skills in children with ID Vuijk et al 2010;Rintala & Loovis 2013) may have resulted in low participation in culturally normative activities like sports (Bouffard et al 1996;Wall 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the complex health and social needs of adults with intellectual disabilities, the low baseline levels of PA and fitness [69] and the increased barriers to PA [70,71] suggests that some generic walking interventions may be inaccessible to adults with intellectual disabilities. Therefore, the design of this walking intervention for adults with intellectual disabilities is distinct from models used in previous general population studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since intellectual disability populations face additional barriers to PA [70,71] and have fewer choices and less control of their health than individuals who do not have intellectual disabilities [72], supporting this group to change PA behaviour may be challenging. For example, a recent weight loss study for adults with intellectual disabilities [73] found that a lack of sufficient support from carers/relatives and poor communication among carers, were identified as being barriers to change.…”
Section: Discussionmentioning
confidence: 99%